(untitled) (Global Journal of Science Frontier Research, 2013)
This paper is devoted to the study of a pathway fractional integral operator associated with the pathway model and pathway probability density for the ℵ-function and a generalized polynomial in the kernel. By specializing the coefficients and various parameters in the generalized polynomials and ℵ-function, our main theorem would readily yield several interesting results.